Assessment of obesity in the indigenous population of the North Region: An integrative review (Research, Society and Development, 2023)
Introduction: Overweight and obesity are becoming a growing problem among indigenous peoples, with evidence of higher rates compared to the general population. Therefore, the objective of this study is to analyze the prevalence of obesity in indigenous populations in the northern region of Brazil. Methodology: This is an integrative literature review that used articles in Portuguese and English indexed in the PUBMED and SciELO databases, as well as Google Scholar. Exclusion criteria were applied to remove articles that did not address the research topic and other types of publications, such as editorials, literature reviews and meta-analyses. Results: 6 articles were selected, 1 of which was a prospective cohort and the other 5 were cross-sectional. The majority of the population studied was composed of indigenous people from the Amazon, followed by groups from different states in Brazil. Discussion: Nutritional deficiencies are a common food problem among indigenous peoples, often accompanied by obesity and metabolic problems. Child malnutrition is especially alarming, with high rates of anemia and stunted growth. Populations in different regions of Brazil have shown high rates of sedentary lifestyle, obesity and overweight, but some tribes such as the Wari' do not show a high prevalence of obesity. Conclusion: Studies on the nutritional health of indigenous peoples in northern Brazil show heterogeneity between ethnicities. New research is needed to understand the causes of these differences and must be carried out in collaboration with indigenous communities to formulate health policies tailored to their needs.